HUBUNGAN MOTIVASI ORANG TUA DENGAN DERAJAT KEJADIAN DEMAM BERDARAH DENGUE PADA ANAK - Masfufah Masfufah; Diah Fauzia Zuhroh; Wiwik Widiyawati (Jurnal Keperawatan Abdurrab, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can be fatal. In a relatively short time, DHF can claim the lives of sufferers if it is not treated as soon as possible. Health is a very important thing in everyday life, to achieve this requires parental motivation to improve health. This study aims to analyze the relationship between parental motivation and the incidence rate of DHF in children. The research instrument in this study used parental motivation questionnaires and DHF incident rate observation sheets. This research is an analytical research with a cross sectional approach. The population is 289 patients, the total sample is 35 patients, using a consecutive sampling technique. The analysis of this study used the Spearman correlation test (p<0.05). The results showed that the motivation of parents to take their children for treatment is that most mothers have strong motivation (65.7%) 33 people, mothers have moderate motivation (28.5%) 10 people and a small proportion of mothers have weak motivation (5.8%) 2 Most people with DHF degree 1 (71%) 25 people, DHF degree 2 (21%) 7 people and DHF degree 3 (8%) 8 people. Statistics show that p = 0.001 is less than 0.05, so H0 is rejected, which means there is a relationship between the level of motivation of parents and the incidence of DHF. So, conclused of this research there is a relationship between parents' motivation and the incidence of DHF in children at Muhammadiyah Gresik Hospital. Keyword :Motivation, DHF insidence